Natural resource curse in Africa: Dutch Disease and institutional explanations - Mulwa, Richard; Mariara, Jane (International Food Policy Research Institute, 2016)
The African continent is endowed with rich natural resources, including minerals and fossil fuels. Production and exports in Africa's resource-rich economies are highly concentrated in natural resource-based products, but these economies show little evidence of structural change toward high value-added activities outside the natural resource sector. Using a sample of 47 African countries, this study aims to explain the impact of natural resources on Africa’s economic growth and other factors explaining growth in the continent in the wake of many natural resource discoveries. We use OLS regressions and seemingly unrelated regressions (SUR) to achieve this objective. In the OLS regressions, the share of primary resource production to GDP; share of mineral production to GDP; share of oil production to GDP; and total share of all natural resources to GDP were used as measures of natural resource endowment. Results indicate that there is a negative but insignificant relationship between the share of total natural resource abundance to GDP and per capita GDP growth. However, when this resource endowment measure is decomposed to individual components, the share of primary production and the share of mineral resources have a negative relationship with GDP growth, while the share of oil production has a positive relationship with growth. This indicates that there is a natural resource curse effect, especially in economies rich in primary resources and mineral resources, but no such effect in oil-rich states. We also test whether this natural resource curse can be explained by market mechanisms (Dutch Disease) or institutional quality mechanisms. Results from this analysis show that improved government effectiveness and an increase in the corruption perception index (i.e., a reduction in corruption) do improve the property rights index GDP growth.